answersLogoWhite

0


Best Answer

-2(cot2theta)

User Avatar

Wiki User

โˆ™ 2013-07-30 11:47:11
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.74
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
1040 Reviews

Add your answer:

Earn +20 pts
Q: What is tan theta minus cot theta?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

How can you verify 1 plus tan theta divided by 1 minus tan theta equals cot theta plus 1 divided by cot theta minus 1?

It depends if 1 plus tan theta is divided or multiplied by 1 minus tan theta.


If tan Theta equals 2 with Theta in Quadrant 3 find cot Theta?

Cotan(theta) is the reciprocal of the tan(theta). So, cot(theta) = 1/2.


If tansqtheta plus 5tantheta0 find the value of tantheta plus cottheta?

tan2(theta) + 5*tan(theta) = 0 => tan(theta)*[tan(theta) + 5] = 0=> tan(theta) = 0 or tan(theta) = -5If tan(theta) = 0 then tan(theta) + cot(theta) is not defined.If tan(theta) = -5 then tan(theta) + cot(theta) = -5 - 1/5 = -5.2


Tan theta plus cot theta equals 2csc2 theta?

Yes, it is.


What is cot theta divided by tan theta plus one equal?

whats the big doubt,cot/tan+1= 1+1= 2


What can the function cotangent theta also be expressed as?

cot theta=tan(90-tetha)


What is sec squared theta times cos squared theta minus tan squared theta?

Tan^2


How do you simplify sin theta times csc theta divided by tan theta?

Since sin(theta) = 1/cosec(theta) the first two terms simply camcel out and you are left with 1 divided by tan(theta), which is cot(theta).


What is tan theta divided by cot theta?

Since CotΘ = 1 / tanΘ, then tanΘ / cotΘ = tanΘ / (1/tanΘ) = tanΘ x tanΘ = tan²Θ


Express csc theta in terms of cot theta theta is in quadrant 3?

It is -sqrt(1 + cot^2 theta)


Sec squared theta plus tan squared theta equals to 13 12 and sec raised to 4 theta minus tan raised to 4 theta equals to how much?

It also equals 13 12.


How do you simplify csc theta cot theta cos theta?

cosec(q)*cot(q)*cos(q) = 1/sin(q)*cot(q)*cos(q) = cot2(q)

People also asked